Digital Health Data: A Comprehensive Review of Privacy and Security Risks and Some Recommendations - Shahidul Islam Khan; Abu Sayed Md. Latiful Hoque (Computer Science Journal of Moldova, 2016)
In today’s world, health data are being produced in ever\-increasing amounts due to extensive use of medical devices generating data in digital form. These data are stored in diverse formats at different health information systems. Medical practitioners and researchers can be benefited significantly if these massive heterogeneous data could be integrated and made accessible through a common platform. On the other hand, digital health data containing protected health information (PHI) are the main target of the cybercriminals. In this paper, we have provided a state of the art review of the security threats in the integrated healthcare information systems. According to our analysis, healthcare data servers are leading target of the hackers because of monetary value. At present, attacks on healthcare organizations' data are 1.25 times higher compared to five years ago. We have provided some important recommendations to minimize the risk of attacks and to reduce the chance of compromising patients' privacy after any successful attack.